Improvement of physical and oral function in community‐dwelling older people after a 3‐month long‐term care prevention program including physical exercise, oral health instruction, and nutritional guidance - Yoshimi Iwao; Hideo Shigeishi; Shouichi Takahashi; Shino Uchida; Shirou Kawano; Masaru Sugiyama (Wiley, 2019)
Abstract Objective There is limited evidence about the most appropriate way to improve physical and oral function in older people. The aim of this study was to clarify the effectiveness of a long‐term care prevention program combining physical exercise, oral health instruction, and nutritional guidance among community‐dwelling older people. Materials and methods We included 43 older people aged at least 65 years (seven men and 23 women; mean age 75.3 years) in Bungotakada City, Japan. The 3‐month program involved a weekly intervention. Physical and oral function was investigated on the first day of the program (i.e., baseline) and at the end of the program (i.e., after 3 months). Physical function was examined using measures such as handgrip strength, timed up‐and‐go test, and one‐leg standing time with eyes open. An oral diadochokinesis test was used to assess oral function. Results Mean maximum handgrip strength increased significantly in older people aged ≤74 years (younger participants) and those aged ≥75 years (older participants) after 3 months compared with the baseline. The timed up‐and‐go test duration was significantly lower in older participants after the program. Repetition of the monosyllables pa and ka and the repetitive saliva swallowing test was significantly improved in both groups. The dysphagia risk assessment for the community‐dwelling elderly score was significantly lower in younger participants after 3 months. Conclusion Participation in a 3‐month program combining physical exercise, oral health instruction, and nutritional guidance may contribute to improvement or maintenance of oral and physical function in older people.